Primary Fallopian Tube Carcinoma Arising in the Setting of Chronic Pelvic Inflammatory Disease - Ibrahim M. Zardawi (Case Reports in Medicine)
Primary fallopian tube cancer (PFTC) is a rare gynaecological malignancy, clinically often mistaken for pelvic inflammatory disease or ovarian cancer. Three primary fallopian tube carcinomas, arising in a background of chronic pelvic inflammatory disease (PID), are presented. The possible association between chronic PID and PFTC is discussed and a hypothesies linking these cancers with chronic inflammation is proposed.